(untitled) (University of Khartoum Engineering Journal, 2022)
Many developments are taking place in the network to meet the 5G (Fifth generation) cellular network requirements; one of the very important research areas is the physical layer architecture and techniques. Studies related to the spectrum efficiency maximization indicate that the 5G air interface technology will also need to be flexible and capable of mapping various services to the best suitable combinations of frequency and radio resources. This paper investigates the physical layer waveform approaches as part of enhanced mobile broadband use case in 5G, and finds the Cyclic-Prefix Orthogonal Frequency Division Multiplexing (CP-OFDM) as a suitable approach by comparing performance parameters where the filtering and windowing can result in degradation of the quality of the signal which is measured via Error Vector Magnitude(EVM). It also attempts to enhance the down link performance between the base station and user equipment by using power amplifier clipping technique, while modelling the downlink channel by implementing channel coding, synchronization signal burst generation, different subcarrier spacing and frame numerologies for different propagation channel and different waveform approaches.